Research and Nursing Care of clients with congestive heart failure: an exploratory study - Liana Amorim Corrêa; Iraci dos Santos; Thais de Oliveira Sousa; Ricardo Mourilhe Rocha; Denilson Campos de Abuquerque (Online Brazilian Journal of Nursing, 2006)
This research had looked for the necessities of nursing care of outpatients with congestive heart failure, through systematic nursing consultation supported in sensible listening. It was an exploratory research using the research/take care technique considering the nursing consultation phases as methodological and technological instruments based on sensible listening theorized by Barbier. Among the cares necessities diagnosis, it was observed that all the citizens had lack of knowledge on its illness and the type of specific diet for its disease. It was confirmed that health education was necessary to be promoted by nursing, not focusing the actions only for physical aspects of the illness. Therefore if using social and sensitivity techniques, costumers can better perceive their necessities not verbalized by themselves.